New directions in the theorisation of temporary urbanisms: Adaptability, activation and trajectory. (October 2021) - Andres, Lauren; Kraftl, Peter
This article rethinks processes and practices of urban temporariness in a more agile, localised and context-specific way, where rhythms and dynamics of the everyday are clearly acknowledged. It discusses the directions of research required to theorise 'temporary urbanisms'. To do so, three overlapping literatures are used: Lefebvrian conceptualisations of rhythms and the everyday; evolutionary analyses of path of change and path creation; and geographies of architecture. This article recognises that although temporariness is (evidently) a universal urban condition, diverse discursive and practical dynamics exist directing urban temporariness along particular channels and shaping space significantly while impacting people's living environments.